Improving Teaching-Learning Process for Digital Signal Processing - Karjigi, Veena; Chandrashekar, H. M. (Journal of Engineering Education Transformations, 2017)
Digital Signal Processing (DSP) is one of the core courses in Electronics and Telecommunication Engineering which involves lot of mathematics. This has led to poor performance of students in the subject. We made an attempt to improve the performance by adopting two main techniques in the teaching-learning process for the subject. First, to overcome the computational mistakes, we gave individual assignments with the same task but different data to every student.We used Matlab to get the answers for all these different data. Second, to make slow learners interact with their better knowledge peers, we made groups of 8 students each and every group was asked to solve 7 questions using Matlab. Along with this graphical user interface was used to explain the applications of DSP. Analysis of results for two consecutive academic years, indicates improvements in the performance of students after adopting these techniques.